Method for refractive index detection for emulsion concentration - Sihai Zhao; Ke Han; Gaopeng Yuan; Lin Wang (Functional Materials, 2018)
The existing approaches to the determination of the oil concentration in the oil-water emulsion (where the dispersed phase is oil) are analyzed in accordance with the theory of light scattering and the change in the refractive index in the suspension. Based on the CCD method, an automatic measuring device was developed to measure the refractive index of the emulsion, the relationship between the concentration and the refractive index of the emulsion was determined.